Analisis Hubungan Profitabilitas Dengan Pergerakan Harga Saham Pada Sektor Usaha PERBANKAN di Bursa Efek Indonesia - Hartono Hartono; Raymundus Parulian Sihotang (Journal of Applied Finance & Accounting, 2009)
Today, stock market activity influenced by many thinks or factors, where could be from internal or external factors company it self. This study analyzed profitability ratio which measured by Net Profit Margin (NPM), Return On Assets (ROA), and Return On Equity (ROE) banking company and the effects to stock market activity. The result showed that only ROE ratio influenced significantly to stock market activity, while others ratio, who is NPM and ROA did not influence significantly to stock market activity.